A comparative evaluation between megadose intravenous dexamethasone and intravenous methyl prednisolone in the treatment outcome of optic neuritis - Panjiyar, P; Sharma, A K; Shrestha, G B; Shah, A (Journal of Chitwan Medical College, 2017)
To compare the efficacy of intravenous methylprednisolone and intravenous dexamethasone for the treatment of optic neuritis in terms of visual recovery and side-effects and to evaluate the clinical profile of optic neuritis patients admitted in BPKLCOS. 60 patients of acute idiopathic typical optic neuritis presenting to our centre were included in this prospective, randomized comparative study. Study population was randomly divided into two groups. Group I received intravenous dexamethasone 200 mg once daily for three days and Group II received intravenous methylprednisolone 500 mg/twelve-hourly for three days followed by oral prednisolone for 11 days. Optic neuritis was found to be common in the age group of 21 to 30 years with female preponderance. The most frequent mode of presentation was abrupt loss of vision. Retrobulbar optic neuritis dominated the study group. Both groups were age and sex-matched. The mean presenting visual acuity in group I was 0.065±0.59. The mean presenting visual acuity in group II was 0.1±0.15. On day 90 of steroid therapy, visual acuity improved to 0.98±0.073 in Group I and 0.88±0.16 in Group II (p=0.23). At three months, there was statistically significant improvement in both groups in terms of colour vision, contrast sensitivity and Goldmann visual fields as well but difference between the two groups was statistically insignificant. Intravenous dexamethasone is an effective treatment for optic neuritis, which is comparable to intravenous methylprednisolone. However, larger studies are required to establish it as a safe, inexpensive and effective modality for the treatment of optic neuritis.